Good deeds done in silence: Stakeholder management and quiet giving by Chinese firms - WANG, Heli (Institutional Knowledge at Singapore Management University, 2021)
We propose a new mechanism explaining why companies may remain silent about their positive corporate behaviors, such as socially responsible activities. We examine such strategic silence in the context of corporate philanthropy. Building on and extending the literature on legitimacy and stakeholder management, we argue that when a firm mistreats primary stakeholders, it is more likely to keep quiet about its philanthropic acts to avoid backlash from stakeholders. We also propose that long-term orientation among stakeholders mitigates the positive relationship between mistreating primary stakeholders and quiet giving, which allows stakeholders to appreciate the long-term value of corporate philanthropy. Data from listed Chinese firms show that firms are more likely to give quietly when they underpay their employees and/or investors. Moreover, research and development expenditures and institutional shareholding, as indicators of stakeholder long-term orientation, attenuate this relationship.